2015
DOI: 10.1021/acs.jpcc.5b08659
|View full text |Cite
|
Sign up to set email alerts
|

Orbital-Resolved Imaging of the Adsorbed State of Pyridine on GaP(110) Identifies Sites Susceptible to Nucleophilic Attack

Abstract: Artificial photosynthesis by photoelectrocatalytic CO2 reduction is dependent, as is natural photosynthesis, on interfacial electron transfer to couple light excitation energy to reaction centers. For heterogeneous systems, in the context of frontier orbital theory artificial reaction centers are defined through the interactions of filled and empty orbitals within a few electronvolts of the Fermi energy of the adsorbate complex. Here we report a scanning tunneling microscopy (STM) and density functional theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…Such ah ypothesis is supportedf urther both by recent predictions from our group [16] and measurements by the Bocarsly group. [11][12][13] These results support the hypothesis of DHP* formation by Py* reduction and the need for an adsorbed co-catalyst (e.g.,D HP*) to shuttle electrons from the surface to CO 2 .T he hypothesis of Py* reduction to DHP* is also supported by the moderate value of the computed reduction potentialf or this process to occur (À0.71 Vv s. the saturated calomel electrode, SCE), [8,9] which lies well below the GaP CB min (À1.76 Vvs. [19] If the CO 2 reduction mechanism in this system were homogeneous,t hen this observation could be explained only by as ubstantial differencei nt he energy of the photoexcited electrons provided by the two surfaces.…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…Such ah ypothesis is supportedf urther both by recent predictions from our group [16] and measurements by the Bocarsly group. [11][12][13] These results support the hypothesis of DHP* formation by Py* reduction and the need for an adsorbed co-catalyst (e.g.,D HP*) to shuttle electrons from the surface to CO 2 .T he hypothesis of Py* reduction to DHP* is also supported by the moderate value of the computed reduction potentialf or this process to occur (À0.71 Vv s. the saturated calomel electrode, SCE), [8,9] which lies well below the GaP CB min (À1.76 Vvs. [19] If the CO 2 reduction mechanism in this system were homogeneous,t hen this observation could be explained only by as ubstantial differencei nt he energy of the photoexcited electrons provided by the two surfaces.…”
Section: Introductionsupporting
confidence: 80%
“…Several adsorptionf ree energy studies found that Py and DHP favorably bind to the GaP surface, whereas CO 2 does not. [11][12][13] These results support the hypothesis of DHP* formation by Py* reduction and the need for an adsorbed co-catalyst (e.g.,D HP*) to shuttle electrons from the surface to CO 2 .T he hypothesis of Py* reduction to DHP* is also supported by the moderate value of the computed reduction potentialf or this process to occur (À0.71 Vv s. the saturated calomel electrode, SCE), [8,9] which lies well below the GaP CB min (À1.76 Vvs. SCE computed for the solvated GaP(110) surface and À1.68 Vv s. SCE computed for the solvated reconstructed GaP(111)s urface).…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations